Rhetoric of the Chinese Cultural Revolution : the impact on Chinese thought, culture, and communication - Lu, Xing, 1956- (Studies in rhetoric/communication., 2004)
"Now known to the Chinese as the "ten years of chaos," the Chinese Cultural Revolution (1966-76) brought death to thousands of Chinese and persecution to millions." "Rhetoric of the Chinese Cultural Revolution identifies the rhetorical features and explores the persuasive effects of political language and symbolic practices during the period. Xing Lu examines how leaders of the Communist Party constructed and enacted a rhetoric in political contexts to legitimize power and violence and to dehumanize a group of people identified as class enemies."